2016
DOI: 10.1126/scisignal.aab0467
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric signaling through an mGlu2 and 5-HT 2A heteromeric receptor complex and its potential contribution to schizophrenia

Abstract: Heterotrimeric guanine nucleotide–binding protein (G protein)–coupled receptors (GPCRs) can form multiprotein complexes (heteromers), which can alter the pharmacology and functions of the constituent receptors. Previous findings demonstrated that the Gq/11-coupled serotonin 5-HT2A receptor and the Gi/o-coupled metabotropic glutamate 2 (mGlu2) receptor—GPCRs that are involved in signaling alterations associated with psychosis—assemble into a heteromeric complex in the mammalian brain. In single-cell experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(150 citation statements)
references
References 68 publications
6
133
1
Order By: Relevance
“…As was shown by Fribourg and colleagues in the Xenopus oocyte expression system [11] (also see [28]), the relative levels of mGlu 2 R and 2AR mRNA injected is a crucial factor of whether the formed heterocomplex would cross-signal or not in response to ligands targeting one or the other receptor. At the optimal mGlu 2 R/2AR mRNA ratio, maximal cross-signaling correlated with the most efficient presentation of each receptor’s protein at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As was shown by Fribourg and colleagues in the Xenopus oocyte expression system [11] (also see [28]), the relative levels of mGlu 2 R and 2AR mRNA injected is a crucial factor of whether the formed heterocomplex would cross-signal or not in response to ligands targeting one or the other receptor. At the optimal mGlu 2 R/2AR mRNA ratio, maximal cross-signaling correlated with the most efficient presentation of each receptor’s protein at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence associating mGlu 2 R with psychosis comes from the antipsychotic effects of strong agonists targeting group II metabotropic glutamate receptors [30,21] and from behavioral studies showing that mGlu 2 R, but not the closely related mGlu 3 R, mediates these antipsychotic-like effects in experimental models of psychosis [8,36,43]. The mGlu 2 and 2A receptors form heteromers in heterologous expression systems as well as in mouse and human frontal cortex [13,29,28]. The physiological significance of this complex is highlighted by behavioral experiments demonstrating that in experimental models of psychosis the antipsychotic-like effects of drugs targeting either receptor require the presence of the partner receptor [11] and that wild-type mGlu 2 R, but not a mutant unable to bind 2AR, can rescue the head-twitch behavior induced by the hallucinogenic 5-HT2 A receptor agonist DOI [29].…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminally c-Myc-tagged form of wild type human 5-HT 2A receptor (pcDNA3.1-c-Myc-5-HT 2A ) has been described previously. 21 …”
Section: Methodsmentioning
confidence: 99%
“…We [36,59,60] and others [12] have confirmed in HEK293 cells that at least a fraction of the populations of mGlu2 and 5-HT 2A receptors constitute part of the same protein complex as defined by co-immunoprecipitation assays (Figure 1D). It has also been demonstrated that these two receptors are expressed in close molecular proximity as defined independently by biophysical assays such as BRET [36], microscope-based FRET [36], flow cytometry-based-FRET [59,60], antibody-based time-resolved FRET [12], and combination of time-resolved FRET and the SNAP-tag approach [33].…”
Section: Family a Gpcr Heteromers And Their Role In Receptor Functionmentioning
confidence: 54%
“…These assays showed that labeling for both 5-HT 2A and mGlu2 receptors was observed in close sub-cellular proximity, particularly at or near synaptic junctions [59]. Using a sub-cellular fractionation approach to purify fractions enriched in presynaptic active zone (PAZ) and postsynaptic density (PSD) proteins, it has recently been confirmed that the 5-HT 2A receptor is detected mostly in the PSD, whereas the mGlu2 receptor is detected in both the PSD and the PAZ fractions [60]. In addition, 5-HT 2A and mGlu2 receptors can be co-immunoprecipitated from mouse [83] and human [36] frontal cortex plasma membrane preparations.…”
Section: Family a Gpcr Heteromers And Their Role In Receptor Functionmentioning
confidence: 99%